Albania’s European Perspective and the Albanian Politics - Nexhipi, Dr. Adelina; Erjon Nexhipi (European Journal of Multidisciplinary Studies, 2019)
Albania’s EU integration has been an important part of politics of all Albanian governments after 1990s. This process has been considered not only as a means for being a part of the United Europe, but a factor for achieving the stability in the country, economic development, strengthening democracy. Diplomatic relation between Albania and the EU were established since 1991, but Albania’s European perspective was ensured only in 1999, by signing the Stabilization and Association Agreement. Since 1999 onwards the Albanian governments have been working for fulfilling the membership criteria to European Union, though the process has been a long and problematic one. Nowadays (2019) Albania expects the EU to open the negotiations for the EU membership process. Through this descriptive-analytical study, we will shed light into the most important moments of the Albanian process toward the European integration; policies followed from both parties, attitudes of the Albanian politics, encountered difficulties, problems and achieved successes. The study relies on the many documents from EU and Albanian institutions such as studies, analyses, interviews with political personalities, Albanian and European researchers and analysts. The study aims to analyze the “long and difficult” path of Albania towards EU, focusing on what has been achieved and the future challenges.